Oil and the World Economy : Some Possible Futures - Kumhof, Michael; Muir, Dirk. (Washington, D.C. : International Monetary Fund, 2012)
This paper, using a six-region DSGE model of the world economy, assesses the GDP and current account implications of permanent oil supply shocks hitting the world economy at an unspecified future date. For modest-sized shocks and conventional production technologies the effects are modest. But for larger shocks, for elasticities of substitution that decline as oil usage is reduced to a minimum, and for production functions in which oil acts as a critical enabler of technologies, GDP growth could drop significantly. Also, oil prices could become so high that smooth adjustment, as assumed in the model, may become very difficult.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet